Total artificial heart in the pediatric patient with biventricular heart failure. (January 2014) - Park, SS; Sanders, DB; Smith, BP; Ryan, J; Plasencia, J; Osborn, MB; Wellnitz, CM; Southard, RN; Pierce, CN; Arabia, FA; Lane, J; Frakes, D; et al.
Mechanical circulatory support emerged for the pediatric population in the late 1980s as a bridge to cardiac transplantation. The Total Artificial Heart (TAH-t) (SynCardia Systems Inc., Tuscon, AZ) has been approved for compassionate use by the Food and Drug Administration for patients with end-stage biventricular heart failure as a bridge to heart transplantation since 1985 and has had FDA approval since 2004. However, of the 1, 061 patients placed on the TAH-t, only 21 (2%) were under the age 18. SynCardia Systems, Inc. recommends a minimum patient body surface area (BSA) of 1.7 m 2, thus, limiting pediatric application of this device. This unique case report shares this pediatric institution's first experience with the TAH-t. A 14-year-old male was admitted with dilated cardiomyopathy and severe biventricular heart failure. The patient rapidly decompensated, requiring extracorporeal life support. An echocardiogram revealed severe biventricular dysfunction and diffuse clot formation in the left ventricle and outflow tract. The decision was made to transition to biventricular assist device. The biventricular failure and clot formation helped guide the team to the TAH-t, in spite of a BSA (1.5 m 2 ) below the recommendation of 1.7m 2 . A computed tomography (CT) scan of the thorax, in conjunction with a novel three-dimensional (3D) modeling system and team, assisted in determining appropriate fit. Chest CT and 3D modeling following implantation were utilized to determine all major vascular structures were unobstructed and the bronchi were open. The virtual 3D model confirmed appropriate device fit with no evidence of compression to the left pulmonary veins. The postoperative course was complicated by a left lung opacification. The left lung anomalies proved to be atelectasis and improved with aggressive recruitment maneuvers. The patient was supported for 11 days prior to transplantation. Chest CT and 3D modeling were crucial in assessing whether the device would fit, as well as postoperative complications in this smaller pediatric patient.